Evaluasi Simpang Bersinyal Taman Sari – Cikapayang Kota Bandung Dengan Analisis VisSim - Yopi Grace Hutahaean; Budi Hartanto Susilo (Jurnal Teknik Sipil, 2021)
Taman Sari - Cikapayang intersection is one of the intersections in Bandung that has traffic problems, namely traffic jams. It can be seen from the length of the long lines at the arms of the Taman Sari - Cikapayang intersection to the Sulanjana intersection which often occurs during rush hour and weekend. Traffic jam occur in the Taman Sari - Cikapayang intersection during weekend because of the large number of cars parked along the Cikapayang road and the front of ??Balubur Town Square (Baltos) area.